2013
DOI: 10.1680/geot.11.p.134
|View full text |Cite
|
Sign up to set email alerts
|

Compacted soil behaviour: initial state, structure and constitutive modelling

Abstract: The paper explores the behaviour of compacted soils throughout the (dry density-water content) compaction plane by means of a conceptual framework that incorporates microstructural information. The engineering properties of compacted soils are described by an initial state in terms of a yielding stress, soil suction and a microstructural state variable. Microstructure is defined by the ratio of microvoid volume to total void volume. The pattern of variation of the microstructural parameter within the compactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
88
1
31

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(127 citation statements)
references
References 38 publications
7
88
1
31
Order By: Relevance
“…Sivakumar [41] observed the same qualitative pattern of behaviour in his experimental tests, with initial wetting-induced swelling followed by wetting-induced collapse compression and then finally more wetting-induced swelling. Conventional models expressed in terms of net [53]) or with both s and Sr (Alonso et al [3]). The evidence presented in Figure 19b suggests that such complexity may be overcome by developing models that use * p as stress state variable and fully account for the coupling between mechanical and water retention behaviour.…”
Section: Simulations Of Experimental Data Of Sivakumar (1993)mentioning
confidence: 99%
“…Sivakumar [41] observed the same qualitative pattern of behaviour in his experimental tests, with initial wetting-induced swelling followed by wetting-induced collapse compression and then finally more wetting-induced swelling. Conventional models expressed in terms of net [53]) or with both s and Sr (Alonso et al [3]). The evidence presented in Figure 19b suggests that such complexity may be overcome by developing models that use * p as stress state variable and fully account for the coupling between mechanical and water retention behaviour.…”
Section: Simulations Of Experimental Data Of Sivakumar (1993)mentioning
confidence: 99%
“…Comparing the behaviour of saturated soils under oedometric compression, it is possible to conclude that the aggregates remain even at high stresses (Otálvaro et al, 2015). According to Alonso et al (2013), if water accesses to an initially compacted dry soil, the microstructure will saturate first, because of the strong affinity between water and clay platelets. As soon as the microvoids in clay aggregates are saturated, any excess water will enter the macropores.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, UNSAT many geotechnical studies have shown that compacted clay forms aggregated structures which behave like large particles inside which water is trapped, being separate to water held in the pendular regime between the particles (both aggregates and larger solid particles). A recent example of such a modelling framework can be found in [14] in which the microstructure is quantified by the ratio of microvoids (i.e. voids within the clay aggregates) to total void ratio, a state parameter on which the stress and suction behaviour can be based.…”
Section: Constitutive Modellingmentioning
confidence: 99%